Spectroscopic studies of tungsten samples exposed to intense deuterium and argon plasma streams - Marchenko, A.; Makhlai, V.; Skladnik-Sadowska, E.; Nowakowska-Langier, K.; Zaloga, D.; Sadowski, M.J. (Вопросы атомной науки и техники, 2019)
The use of tungsten (W) as the main plasma facing component (PFC) was proposed for fusion reactors many years ago. Our recent experiments have been focused on spectroscopic studies of tungsten properties under its irradiation by intense plasma streams. Several samples made of pure W or (90 %W + 10 %Cu) alloy have been exposed to deuterium and argon plasma streams generated by the RPI-IBIS multi-rod plasma injector at different experimental conditions. The optical emission spectroscopy (OES) measurements have been carried out as a function of a plasma-stream energy density. The plasma electron density was estimated on the basis of the Stark broadening of the Dβ and Dα spectral lines in a deuterium-plasma stream propagating freely, i.e. without any target, as well as near the irradiated tungsten surface. In this paper the results of a surface analysis of the tungsten samples after their irradiation by pulsed plasma-ion streams, and the influence of those streams on physical and mechanical properties of the irradiated samples, are discussed. A relationship of the structure and properties of the modified surfaces with parameters of the incident plasma-streams is also analyzed.